Distinct HIV-1 Escape Patterns Selected by Cytotoxic T Cells with Identical Epitope Specificity - Yagitaa, Yuichi; Kusea, Nozomi; Kurokib, Kimiko; Gatanagaa, Hiroyuki; Carlson, Jonathan M.; Chikataa, Takayuki; Brummee, Zabrina L.; Murakoshia, Hayato; Akahoshia, Tomohiro; Pfeiferd, Nico; Mallalg, Simon; Johng, Mina; et al. (Journal of Virology, 2013)
Pol283-8-specific, HLA-B*51:01-restricted, cytotoxic T cells (CTLs) play a critical role in the long-term control of HIV-1 infection. However, these CTLs select for the reverse transcriptase (RT) I135X escape mutation, which may be accumulating in circulating HIV-1 sequences. We investigated the selection of the I135X mutation by CTLs specific for the same epitope but restricted by HLA-B*52:01. We found that Pol283-8-specific, HLA-B*52:01-restricted CTLs were elicited predominantly in chronically HIV-1-infected individuals. These CTLs had a strong ability to suppress the replication of wild-type HIV-1, though this ability was weaker than that of HLA-B*51:01-restricted CTLs. The crystal structure of the HLA-B*52:01-Pol283-8 peptide complex provided clear evidence that HLA-B*52:01 presents the peptide similarly to HLA-B*51:01, ensuring the cross-presentation of this epitope by both alleles. Population level analyses revealed a strong association of HLA-B*51:01 with the I135T mutant and a relatively weaker association of HLA-B*52:01 with several I135X mutants in both Japanese and predominantly Caucasian cohorts. An in vitro viral suppression assay revealed that the HLA-B*52:01-restricted CTLs failed to suppress the replication of the I135X mutant viruses, indicating the selection of these mutants by the CTLs. These results suggest that the different pattern of I135X mutant selection may have resulted from the difference between these two CTLs in the ability to suppress HIV-1 replication.